Menggali Potensi Lokal Kota Melalui Pengembangan UMKM Kampung Semanggi Surabaya - Agizca Aurel Syerinatasya; Dina Septiani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Creative industries are industries that rely on the skills, creativity and talents of individuals to generate employment and prosperity. The government has launched the concept of "Creative Economy Indonesia" which is oriented towards creativity and cultural heritage. The culinary industry is the largest subsector in Indonesia's creative industry with a contribution of 41.69% to the national GDP. In the midst of the pandemic, the culinary industry grew positively by 2.95%, showing its resilience. The rapid growth of the culinary industry is characterized by the emergence of many culinary MSMEs. Surabaya is a culinary-rich city with many culinary MSMEs that support the local economy. One of Surabaya's culinary specialties is pecel semanggi. In Semanggi Village, there are many MSMEs made from clover raw materials. The problem faced is the lack of marketing and utilization of local potential and synergy with government programs. Although Semanggi Village is still considered less capable in utilizing local potential, both facilities and synergies with government programs, local MSMEs have made various efforts to market processed clover products, such as through the creation of websites and sales on social media platforms. The development of Kampung Semanggi has been very rapid in terms of products that are increasingly diverse and reach all circles, increasingly modern ways of marketing products by utilizing technology, and the existence of a website that can increase sales of clover products.